Pubg Fansubtitle: Strategies and Translation Acceptability - Puri, Dinda Adventina Laksita; Pasaribu, Truly Almendo (Journal of Language and Literature, 2019)
This study analysed the subtitling strategies and the acceptability of Indonesian fan subtitle in PewDiePie PUBG video entitled â€œI WON!!!â€. There were ten subtitling strategies appearing in the subtitle: Transfer (40.9%), taming (22.3%), deletion (11.3%), expansion (7.9%), paraphrase (5.8%), condensation (2.7%), imitation (2.7%), resignation (1.2%), transcription (0.6%), and decimation (0.6%). The researcher also found four translation acceptability degrees in the subtitle: Ideal-acceptable (80,2%), acceptable (3,7%), unacceptable (9.8%), and failed (6.4%). Therefore, the Indonesian subtitle of â€œI WON!!!â€ is considered as acceptable translation because 83.9% of the translations are acceptable and the effective subtitling strategy to make acceptable translation is transfer.